METHODS OF EFFECTIVE USE OF THE INFORMATION SYSTEM IN IMPROVING THE QUALITY OF MEDICAL SERVICES - Safarov Ulug‘bek Qarshiboy o‘g‘li; Otaxonov Polvonnazir Ergash o‘g‘li; Korabayev Avazbek Alijon o‘g‘li; Bozarov Ulugbek Alisher o‘g‘li (Web of Journals Publishing, 2024)
The article discusses the issues of improving the electronic information system for the effective organization of the educational process in medical universities, the use of innovative technologies in medical education, the introduction, application, assessment and organization of medical education based on effective innovative technologies.
Keywords: form of education, method, technique, electronic didactic support, information system.